2021
DOI: 10.1002/ajcp.12521
|View full text |Cite
|
Sign up to set email alerts
|

The Substance and Circumstances of Race and Immigration Talk in High School Gender and Sexuality Alliances

Abstract: Gender & Sexuality Alliances (GSAs) are school‐based clubs that support youth of diverse sexual orientations and gender identities. As identity‐centered spaces, GSAs could also foster discussions related to race and immigration (i.e., race and immigration talk). We conducted semi‐structured interviews from 2016 to 2018 with 38 GSA members (ages 13–20 years old) of diverse racial/ethnic, immigrant‐origin (first and second generations in the United States born of immigrant parents), sexual orientation, and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Research published in AJCP has aimed to examine how context shapes well-being for LGBTQ individuals at various levels of the socio-ecological model (Bronfenbrenner, 1977), including the relationship level (e.g., familial rejection among sexual minority women; Zimmerman et al, 2015), within community contexts (e.g., religious congregations; Foster et al, 2015), and at the societal levels (e.g., anti-gay political campaigns; Russell & Richards, 2003). This approach aligns with many current conceptualizations of LGBTQ health disparities which focus on structural stigma and the interaction of individuals with their social environments (e.g., minority stress theory; Brooks, 1981;Meyer, 2003). Overall, these studies in AJCP have continued to push beyond conceptualizing social problems as originating within the individual (e.g., holding individuals responsible for their oppression) to instead understand the individual within context.…”
Section: Identities Within Contextmentioning
confidence: 91%
See 2 more Smart Citations
“…Research published in AJCP has aimed to examine how context shapes well-being for LGBTQ individuals at various levels of the socio-ecological model (Bronfenbrenner, 1977), including the relationship level (e.g., familial rejection among sexual minority women; Zimmerman et al, 2015), within community contexts (e.g., religious congregations; Foster et al, 2015), and at the societal levels (e.g., anti-gay political campaigns; Russell & Richards, 2003). This approach aligns with many current conceptualizations of LGBTQ health disparities which focus on structural stigma and the interaction of individuals with their social environments (e.g., minority stress theory; Brooks, 1981;Meyer, 2003). Overall, these studies in AJCP have continued to push beyond conceptualizing social problems as originating within the individual (e.g., holding individuals responsible for their oppression) to instead understand the individual within context.…”
Section: Identities Within Contextmentioning
confidence: 91%
“…In the qualitative analyses, Calzo and colleagues proposed that having advisors or leaders within these spaces that foster these discussions can promote engagement in these conversations. Additionally, researchers suggest shifting away from a conceptualization of Gender and Sexuality Alliances as just “Safe Spaces” and shift to being “Brave Spaces,” where members are encouraged to speak about issues such as racism or xenophobia within spaces with the ultimate goal of ensuring that spaces are safe for all (Calzo et al, 2021).…”
Section: Identities Within Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating race and immigration talk into GSAs can create more inclusive environments (Calzo et al, 2021). A collection of semistructured interviews conducted by Calzo and colleagues (2021) revealed that students of color and immigrant‐origin students experience invalidation and feelings of being unrepresented due to a lack of race and immigration discussions in GSAs.…”
Section: Articulating a Mtss Model To Support Lgbtqia+ Youthmentioning
confidence: 99%
“…The relationship between GSA membership racial diversity and the racial diversity of the community in which GSAs and schools are located remains opaque, with research indicating that the "frequency of meeting attendance did not differ by race/ethnicity for LGBTQ students" (Truong et al, 2021, p. xvii). However, experiences within GSAs may vary, whether due to a "lack of representation and respectful discourse" (Endo, 2020, p. 39) of the intersection of students' racialized, gender, and sexual identities, or what students prioritize as meaningful club activities based on their own identities (Calzo et al, 2021;Chong et al, 2019). GSAs "can help encourage students to be curious about difference," yet students "need to be encouraged to work beyond the exclusions that they may act out, whether racism, sexism, transphobia, or other biases" (C. Mayo, 2014, p. 88).…”
Section: Gsas and Racially Minoritized And Gender-diverse Studentsmentioning
confidence: 99%